2018
DOI: 10.1016/j.yexcr.2017.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal potency analysis of mesenchymal stromal cell function during ex vivo expansion

Abstract: Adult bone marrow mesenchymal stromal cells (MSCs) have cross-functional, intrinsic potency that is of therapeutic interest. Their ability to regenerate bone, fat, and cartilage, modulate the immune system, and nurture the growth and function of other bone marrow hematopoietic stem/progenitor cells have all been evaluated by transplant applications of MSCs. These applications require the isolation and expansion scaled cell production. To investigate biophysical properties of MSCs that can be feasibly utilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…An in vitro model of low-density MSC growth was for example recently used to evaluate the effect of age on a series of MSC biophysical properties used as predictors of bioactivity. The findings of the study indicated that MSC age is a predictor of adipogenesis, while cell and nuclear shape are strongly associated to hematopoietic-supportive potency [204].…”
Section: Pcr Followed By Gelmentioning
confidence: 84%
“…An in vitro model of low-density MSC growth was for example recently used to evaluate the effect of age on a series of MSC biophysical properties used as predictors of bioactivity. The findings of the study indicated that MSC age is a predictor of adipogenesis, while cell and nuclear shape are strongly associated to hematopoietic-supportive potency [204].…”
Section: Pcr Followed By Gelmentioning
confidence: 84%
“…There is convincing evidence that the duration of culture expansion influenced ADSC phenotype and ascertained the relationship between morphological changes and physiological effect [22,[40][41][42] which might explain the mechanisms whereby ADSC ensure tissue repair. Nevertheless, cryopreservation effect on expanded ADSC physiology should not be excluded adding to the complexity of their physiologymicroenvironment interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the usefulness of these criteria for identifying MSCs, these cell populations are reported to be heterogenous with regard to their non-clonal proliferation, differentiation potencies, stromal stem cell profiles and committed progenitors [117,118]. These differences appear to be related to their tissue origin and to the cell separation and culture expansion techniques used [119,120]. Thus, the complex composition of the exosomes released is markedly influenced by initial local cell crosstalk and microenvironmental priming.…”
Section: Exosomes Derived From Mesenchymal Stem/stromal Cells Of Diffmentioning
confidence: 99%